D-dimer serves as predictor of plastic bronchitis or necrotizing pneumonia in children with Mycoplasma pneumoniae pneumonia - Yue, Yanke; Lian, Tiantian; Kang, Lei; Liu, Shuai; Geng, Wenjin; Xu, Meixian (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to explore risk factors for plastic bronchitis (PB) or necrotizing pneumonia (NP) in children with Mycoplasma pneumoniae pneumonia (MPP).MethodsThis is a retrospective, observational cohort study, which was conducted at the Hebei Children's Hospital, Shijiazhuang, Hebei, China. This study compared the clinical characteristics between children with MPP who developed PB or NP and children with MPP who did not develop PB or NP. Variables with a P-value <0.1 in the univariate logistic regression analysis were further analyzed in the multivariate logistic regression analysis.ResultsOne hundred and seven hospitalized children with MPP were retrospectively enrolled in this study. Three (3/107, 2.80%) patients were admitted with severe pneumonia, and sixty-nine (69/107, 64.49%) patients required for non-invasive ventilation after admission. The incidence of macrolide-unresponsive Mycoplasma pneumoniae pneumonia (MUMPP) was 39.25% (42/107), and the incidence of refractory Mycoplasma pneumoniae pneumonia (RMPP) was 9.35% (10/107). Thirteen (13/107, 12.15%) patients were diagnosed with PB or NP during hospitalization. Logistic regression analysis showed that the D-dimer (DD) level [odds ratio [OR] 1.28, 95% confidence interval [CI] 1.07–1.61; P = 0.013] was independently and positively associated with the risk of PB or NP occurring. Receiver operating characteristic (ROC) analysis showed that the best cutoff point for D-dimer in predicting PB or NP is 2.44 (mg/L) (AUC = 0.85, 95% CI: 0.76–0.95, sensitivity: 92.31%, specificity: 75.53%, P < 0.001*).ConclusionsThis study found that the elevated DD level (≥2.44 mg/L) has a predicting value for the progression of children with MPP to the composite outcome of PB or NP. However, due to the limited number of PB cases, its specific prediction for PB needs further verification.